The Kernel of the Joint of Two Operators - Yogendra Prasad Shah; Sanju Kumar Singh (ABM: International Journal of Administration, Business and Management, 2024)
This study explores the differences between kernel intersections and individual kernel spaces in Hilbert spaces. These differences are crucial for understanding the relationship between linear operators and their compositions. The main findings establish necessary conditions for the inequality dim (Ker (AB)) ≥ dim (Ker(A)) + dim (Ker (B) ∩ B′) to hold, where A and B are bounded linear operators, Ker denotes the kernel, and B′ is the image of B. The proofs rely on Hilbert space properties, closed subspaces, and operator ranges. Although the results are presented in the context of Hilbert spaces, the authors discuss potential extensions to other spaces with similar properties. The paper concludes by emphasizing the broader relevance of these inequalities in various fields of mathematics, including functional analysis, optimization, and potentially other disciplines that deal with continuous quantities.